Determinants of preterm premature rupture of membranes among pregnant women at public hospitals in the Sidama Region, Ethiopia - Kidist Gebre; Desalegn Dawit Assele; Ephrem Lejore; Wondwosen Teklesilasie (Therapeutic Advances in Reproductive Health, 2025)
Background: Preterm premature rupture of membranes (PPROM) is a significant risk factor for perinatal morbidity and mortality. It is the main cause of preterm birth and affects approximately 10% of all pregnancies. The occurrence of PPROM has recently increased significantly. However, there is limited data on the determinants of PROM in the study area. Objective: To assess the determinants of PPROM, among pregnant women admitted to maternity wards of public hospitals in the Sidama Region. Design: An institution-based, unmatched case–control study Methods: The study was conducted in public hospitals in the Sidama Region from March 1st to May 15th, 2023. The consecutive cases were recruited until the required sample size was reached, and controls were randomly selected. Face-to-face interviews were used to collect data from 69 cases and 207 controls. Binary logistic regression analysis was used to identify determinants of PPROM. An adjusted odds ratio (AOR) with a 95% confidence interval (CI) was reported to show the strength of the association. The significance of the association was declared at a p value <0.05. The goodness-of-fit model was checked by the Hosmer–Lemeshow test. Results: A total of 69 cases and 207 controls were included in the study. Pregnancy-induced hypertension (AOR: 2.65; 95% CI: 1.12–6.27), a history of abortion (AOR: 3.1; 95% CI: 1.41–7.08), a history of abortion (AOR: 3.78; 95% CI: 1.75–8.15), a history of cesarean section (AOR: 2.57, 95% CI: 1.10–5.99), a mid-upper arm circumference <23 cm (AOR: 2.1; 95% CI: 1.02–4.54), a history of urinary tract infection (AOR: 2.42; 95% CI: 1.10–5.32), and a hemoglobin level <11 mg/dl (AOR: 2.68; 95% CI: 1.15–6.23) were determinants of PPROM. Conclusion: Past obstetric history, nutritional status, and risks in the index pregnancy have an association with PPROM. Therefore, strategies to reduce the occurrence of PPROM should target women in rural areas and emphasize the early identification and treatment of urinary tract infections, anemia, and pregnancy-induced hypertension.